PENGARUH KOMPENSASI, MOTIVASI, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DI SMPIT NUR HIDAYAH SURAKARTA - Rosnendya Yudha Wiguna; Istiatin; Sudarwati (JURNAL ILMIAH EDUNOMIKA, 2025)
The problem formulation in this study is as follows does compensation affect teacher performance?, does motivation affect teacher performance?, does organizational culture affect teacher performance?, does the work environment affect teacher performance?. This study uses a descriptive quantitative approach. The research was conducted at SMPIT Nur Hidayah Surakarta. A total of 46 respondents were selected using a saturated sampling technique. The research findings indicate that compensation does not have a significant effect on teacher performance. This suggests that the teachers at SMPIT Nur Hidayah are not primarily driven by financial factors in carrying out their duties. Their performance tends to remain consistent despite differences or changes in the compensation they receive. Motivation has a significant effect on teacher performance. High motivation, both intrinsic and extrinsic, has been proven to increase teachers’ work enthusiasm, sense of responsibility, and dedication in the learning process. Organizational culture also significantly affects teacher performance. A work culture that is religious, cooperative, and aligned with the school’s vision and mission has been shown to support teachers in improving their performance, both in teaching and in guiding students. The work environment does not have a significant effect on teacher performance. This may be due to the fact that the school’s work environment is generally perceived as sufficiently supportive, and thus is not a determining factor in the improvement or decline of teacher performance. Keywords: Compensation, Motivation, Organizational Culture, Work Environment, Performance